Behaviour of large-area avalanche photodiodes under intense magnetic fields for VUV- visible- and X-ray photon detection - Fernandes, L. M. P. (2003)
The behaviour of large-area avalanche photodiodes for X-rays, visible and vacuum-ultra-violet (VUV) light detection in magnetic fields up to 5 T is described. For X-rays and visible light detection, the photodiode pulse amplitude and energy resolution were unaffected from 0 to 5 T, demonstrating the insensitivity of this type of detector to strong magnetic fields. For VUV light detection, however, the photodiode relative pulse amplitude decreases with increasing magnetic field intensity reaching a reduction of about 24% at 5 T, and the energy resolution degrades noticeably with increasing magnetic field.